The gingival crevicular fluid levels of growth factors in patients with amlodipine-induced gingival overgrowth: A pilot study - YILDIRIM, HATİCE SELİN; KÖSE, KEMAL NACİ; KURU, LEYLA; AĞRALI, ÖMER BİRKAN (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2020)
Background: Amlodipine, calcium channel blocker (CCB), is used in the management of cardiovascular diseases which causes gingival overgrowth (GO). The growth factors may have a role in the pathogenesis of amlodipine-induced GO. Objectives: This pilot study aimed to investigate the growth factors including transforming growth factor-b1 (TGF-b1), platelet-derived growth factor-BB (PDGF-BB), and basic fibroblast growth factor (bFGF) in gingival crevicular fluid (GCF) of patients with amlodipine-induced GO and compare with of healthy subjects. Methods: GCF samples were collected from 56 sites presenting GO (GO + group) and from 38 sites not presenting GO (GO- group) of 5 patients using amlodipine for more than one year, and from 45 sites (control group) of 5 healthy subjects. The levels of TGF-b1, PDGF-BB, and bFGF were determined by using ELISA kits. Results: The mean concentration of TGF-b1 in GCF samples of GO + group (9.50 +/- 7.30 ng/ml) was higher than both GO- group (2.07 +/- 0.50 ng/ml) and control group (2.74 +/- 1.01 ng/ml) (P = 0.014). No significant difference was found among the groups in the GCF levels of PDGF-BB (P = 0.767). bFGF was detected in only 33% of the sites from patients. Conclusion: These preliminary results suggest that TGF-b1 may play a crucial role in the pathogenesis of amlodipine-induced GO.
Keywords: Amlodipine; Gingival overgrowth; growth factors; CALCIUM-CHANNEL BLOCKERS; FACTOR-BETA; CYCLOSPORINE-A; EXPRESSION; HYPERPLASIA; PREVALENCE; PHENYTOIN; PATHOGENESIS; NIFEDIPINE; TISSUES